Effects of osmotic pre-treatment and vacuum frying condition on the quality of pumpkin chips - Pattaraporn Piyalungka; Nguyen, Loc Thai; Anal, Anil Kumar; Sadiq, Muhammad Bilal; Rittichai Assavarachan; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The research was to improve qualities of vacuum - fried product s using osmotic and ultrasonic - assisted osmot ic dehydration as pre - treatment of pumpkin prior to frying. The effects of osmotic and ultrasonic - assisted osmotic dehydration conditions (maltodextrin concentration, temperature, time) on th e water loss and solid gain of pumpkin and optimization the conditions were studied. It could conclude that concentration of maltodextrin and solution temperature were the most important factors that significantly affected the water loss and solid gain dur ing both osmotic dehydration with and without applied ultrasonic, while the immersion time showed less effect. The osmotic dehydration at 35 o C for 90 min and ultrasonic - assisted osmotic dehydration at 55 o C for 30 min using concentration of maltodextrin at 40 % (w/v) were the optimum pre - treatment conditions. During frying process, moisture content, water activity, lightn ess, yellowness, and carotenoid content of pumpkin chips decreased with increasing frying temperature and time while oil content, hardnes s, and redness increased. The osmotic pre - treatments with and without applied ultrasonic had the advantage in term of reduction oil content, improving color, and preservative carotenoids in the pumpkin chips. The frying at 100 o C for 30 min was the optimum condition for the fried sample with and without osmotic pre - treatment, while the optimum frying condition for the fried sample with ultrasonic - assisted osmotic pre - treatment was 100 o C for 20 min. Both untreated and osmotic trea ted fried sample were not differenced in the microstructure, while ultrasonic - assisted osmotic treated fried sample appear s to have more pore and more damaged in the cell tissue. The change in qualities of pumpkin chips both with and without pre - treatment during difference storage conditions (temperature and time) found that as an increase in storage temperature lead ed to an increase moisture content, peroxide value, hardness , and redness, while lightness and yellowness decreased throughout storage time. T he change in all qualities of the treaded fried sample showed no significant difference with the untreated fried sample during storage. The treaded fried sample showed higher kinetic reaction rate in term of moisture content, peroxide value, lightness, and hardness, while redness and yellowness showed lower as compared to the untreated fried sample. The shelf - life of the fried sample without pre - treatment shorter than the fried sample with pre - treatment.
A thesis submitted in partial fulfillment of the requirements for the d egree of Master of Engineering in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2017
Keywords: Pumpkin; Food -- Drying; Ultrasonic waves